Estimating the effect of population age distribution on CO2 emissions in developing countries - Yaqoob, Mohammad; Mhd Bani, Nor Yasmin; Ishaq, Suryati; Rosland, Anitha (Taylor and Francis Ltd., 2024)
This study evaluates the effect of the population’s age structure on CO2 emissions based on the panel data of 82 developing nations between 1990 and 2019. We use 20–34, 35–49, 50–64, and 65 and above as four population age groups. The findings from the dynamic common correlated effect (DCCE) estimator show a positive association between the ratios of the population aged 20–34, 35–49, and 50–64 years with CO2 emissions. The results also exhibit the heterogeneous impacts of the population’s age structure on the CO2 emissions for lower-income and higher-income countries. For instance, people aged 20–34 and 35–49 years in lower-income countries are responsible for an increase in CO2 emissions, and the population over age 65 and age 50–64 years are associated with an increase in the CO2 emissions in higher-income countries. The additional findings indicate that urbanisation, energy consumption, and economic growth are other factors that adversely affect the environment. Based on this evidence, to mitigate the aggregate CO2 emissions, the governments of these nations must pay close attention to the population’s age distribution.